HUBUNGAN ANTARA VARIASI IKLIM DENGAN KEJADIAN ASMA DI KOTA SEMARANG TAHUN 2011-2015 (Studi Kasus di Wilayah Kerja Puskesmas Bandarharjo Kota Semarang) - Rani Novianis Rizky Saputri; Budiyono Budiyono; Suhartono Suhartono (Jurnal Kesehatan Masyarakat (Undip), 2016)
Puskesmas Bandarharjo is one area that has the incidence of asthma is quite high numbered at 596 cases in 2015. The climate can affect respiratory diseases including asthma. Climate conditions in Semarang during 2002-2011 has changes including air temperature increased an average of 0.1°C annually and the humidity has increased an average of 1.6% annually.The purpose of this research was to analyze the relationship between climate variabilities are the incidence of asthma in Puskesmas Bandarharjo Semarang during 2011-2015.The research was cross sectional research. Data of climate obtained from Indonesian Agency for Meteorological, Climatological and Geophysics of Semarang, at the station of taking in Tanjung Mas. Data of asthma incidence was taken in Puskesmas Bandarharjo. Statistical analysis using rank Spearman with α = 0.05.The results showed that the average air temperature during 2011-2015 was amounted 28.1°C, the average humidity was 76.1%, the average rainfall was 180.3 mm/month. There was a negative correlation between variation in temperature with the incidence of asthma (p = 0.251 and r = -0.151), there was a positive correlation between the humidity with the incidence of asthma (p = 0.264 and r = 0.146), there was a positive correlation between rainfall and the incidence of asthma (p = 0.369 and r = 0.118). The research concluded that there was no correlation between Climate variations with the incidence of asthma and increased incidence of asthma was negatively correlated with an air temperature enhancement in Puskesmas Bandarharjo in Semarang during 2011-2015